1999
DOI: 10.33338/ef.84008
|View full text |Cite
|
Sign up to set email alerts
|

New species and new or interesting records of click-beetles from Iran and Iraq (Coleoptera, Elateridae)

Abstract: This paper provides new records and descriptions of eight new species of clickbeetles (Coleoptera, Elateridae) from Iran and Iraq. The species are grouped according to tribes and the new taxa belong to the genera Calais Castelnau, Idotarmonides Agajew, Melanotus Eschscholtz, Craspedostethus Schwarz, Dicronychus Brullé; new names are proposed for two species of Cardiophorus Eschscholtz (preoccupied).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Recently, the fauna of Elateridae and Eucnemidae of Southeast Europe has been intensively studied, including descriptions of new species, and reports of the new country records (e.g., Kovács et al 2014, Mertlik et al 2015, Platia 2011, 2016. During the identifi cation of material from recent collecting trips of the authors as well as the material from different collections, we found several new distributional records for Elateridae and Eucnemidae.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Recently, the fauna of Elateridae and Eucnemidae of Southeast Europe has been intensively studied, including descriptions of new species, and reports of the new country records (e.g., Kovács et al 2014, Mertlik et al 2015, Platia 2011, 2016. During the identifi cation of material from recent collecting trips of the authors as well as the material from different collections, we found several new distributional records for Elateridae and Eucnemidae.…”
Section: Introductionmentioning
confidence: 61%
“…Distribution -E: HU PL SK (Cate 2007) CZ (Dušánek 1999 Distribution -E: AU BU CT CZ FR GE GB HU IT LT PL RO SK SP SV SZ UK (Cate 2007) GR (Platia 2011).…”
Section: Cardiophorus Nigerrimus Erichson 1840mentioning
confidence: 99%
“…Additionally, we find Coptostethus , until now a subgenus of Cardiophorus , as phylogenetically distinct from Cardiophorus (Figs ,S1). Some authors already treated Coptostethus as a separate genus, but without analysis or other evidence (Dajoz ; Németh & Platia ; Platia & Kakiopoulos ; Platia ). Coptostethus was originally defined by the short wings of its species (Wollaston ), with most representatives known from the Canary Islands (Cobos , , ).…”
Section: Discussionmentioning
confidence: 99%
“…nov. ; C. longicornis Lindberg, 1953; Coptostethus machadoi (Cobos, ) comb. nov. ; C. mantici Platia, ; Coptostethus mateui (Cobos, ) comb. nov. ; Coptostethus mendizabali (Cobos, ) comb.…”
Section: Taxonomymentioning
confidence: 99%
“…Population density and species composition of Elateridae family in particular areas depend on a variety of ecological factors, and the most important factors are climatic and micro-climatic conditions existing in certain habitats (Lawrence et al, 2007;Platia, 2011), temperatures and soil specifications. This is particularly evident in natural habitats where resources are intact and mostly unaffected by human influence (Platia & Gudenzi, 2005).…”
Section: Introductionmentioning
confidence: 99%